"You are already all you need to be": A case illustration of compassion‐focused therapy for shame and perfectionism. Issue 11 (14th September 2020) - Matos, Marcela; Steindl, Stanley R.
Abstract: This paper presents the case of a 28‐year‐old woman diagnosed with major depressive disorder, with strong features of perfectionism, shame, and self‐criticism, treated via 12 sessions of compassion‐focused therapy (CFT). CFT is an integrative therapeutic approach that draws upon evolutionary psychology, attachment theory, and applied psychological processes from neuroscience, clinical and social psychology. The effectiveness of compassion focused approaches with perfectionism and self‐criticism across a range of clinical disorders is becoming increasingly well‐established. Given this mounting evidence, a four‐phase, 12‐session CFT treatment plan was developed for this case: (1–2) establishing the therapeutic relationship; (3–4) psychoeducation regarding the evolutionary model of compassion; (5–8) compassionate mind training and skills development; (9–11) working with perfectionism, shame, and self‐criticism. A follow‐up session focused on envisioning a compassionate future. Therapeutic process and clinical outcome will be discussed, as well as implications for using CFT in clinical practice, especially where perfectionism, shame, and self‐criticism are part of the clinical presentation.